Non-Destructive Test of Seawater Concrete Containing Rice Husk Ash and Coal Bottom Ash as Cement and Sand Replacement - Nurazuwa Md Noor; Eviria Fredereick Gan (Journal of Structural Monitoring and Built Environment, 2024)
The high demand for concrete production induced high consumption of freshwater, river sand, and cement. This had resulted in harmful issues for the environment such as a high carbon footprint, water shortage, greenhouse effect, and more. These negative impactions for environment had led to the use of rice husk ash (RHA) and coal bottom ash (CBA) as a replacement for cement and sand respectively. The main objective of this study is to investigate the concrete quality through the non-destructive test (NDT). Concrete with seawater, RHA, and CBA was tested on its surface and internal strength using rebound hammer test and ultrasonic pulse velocity test respectively. To achieve the objective, seven (7) series of mixtures were prepared. RHA is fixed to 10% of cement replacement by weight, while the volume of sand is replaced CBA by 10% increment up to 100%. All specimens are tested at 7 and 28 days. In addition, NDT’s result was later compared with compressive strength. The outcomes of this investigation shown that regression values (R2) more than 0.85 sufficiently indicate the relationship between the non-destructive test and compressive strength. As a result, the seawater concrete combining RHA and CBA produced by this study has a good quality and compressive strength. Hence, this study offered environmentally friendly materials, seawater, rice husk ash, and coal bottom ash are presented as eco-materials in concrete to partially replace conventional materials.